Family Politics in the Recruitment Process of Legislative Candidates in the 2024 Elections: A Case Study of the Indonesian Unity Party (Perindo) - Subekti, Dimas; Putra, Dinda Syufradian; Muliono, Muliono (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to explain the political recruitment process of the Perindo Party in endorsing legislative candidates with the family backgrounds of its general chairman. This research uses a qualitative method with a case study approach. The results showed that the Perindo Party normatively implemented a more innovative political recruitment process for the 2024 legislative elections by involving public participation and technology. However, in this idealized process, a phenomenon of family politics occurs. The family of the chairman of the Perindo Party did not go through the entire recruitment process because they have strong ties to the party elite who have decision-making power. The chairman's family jumped straight to the nomination stage to be nominated by the Perindo Party. The mechanism is also directly through appointment rather than e-voting as cadres and the general public must go through the title of the people's convention. Therefore, the political recruitment of the Perindo party for the 2024 legislative elections has a gap in the process for the chairman's family because it does not apply the principles of openness and fairness. This has implications for the lousy party institutionalization trend in political recruitment.